STRATEGI PEMBELAJARAN BAHASA ARAB BAGI ANAK BERKEBUTUHAN KHUSUS DI KELAS II SD ISLAM AL MADANI BANJARBARU - Rusma Yulidawati; Wilda Rahmatina (Tarbawi, 2023)
This study is a qualitative descriptive field study focusing on Arabic learning strategies for children with special needs with social communication disorders in grade II by SD Islam Al Madani Banjarbaru. The data in this study are data related to Arabic learning strategies for children with special needs and the data source is SD Islam Al Madani grade II Arabic language teachers and special tutors Banjarbaru. Data collection techniques include observation, interview, and note-taking. The results of this study in which Arabic teachers used Arabic learning strategies for children with social communication disorders in Grade II of Al Madani Islamic Primary School applied the CTL strategy and Collaborative learning strategy with an orientation towards teacher creativity and the use of diverse and creative media. The barriers that teachers face when teaching Arabic are the environment that does not support learning during the day as well as psychological and emotional factors for children with special needs when feelings of guilt and anxiety arise bad mood.